FENOMENA DIGLOSIA PADA TUTURAN SISWA KELAS 12 IBB MAN 1 PROBOLINGGO DALAM KEGIATAN BELAJAR MENGAJAR MAPEL BAHASA INDONESIA - Aisyah, Siti; Juwaeni, Juwaeni (ASMARALOKA: Jurnal Bidang Pendidikan, Linguistik, dan Sastra Indonesia, 2023)
Diglossia is a discussion of the human ability to communicate in several different language codes in a society, which means a state of society where there are two variations of one language that coexist and each has a certain role. There are two types of diglossia, namely the T function for formal situations and the R type for casual situations. One of the uses of the T variety is when teaching and learning takes place at MAN 1 Probolinggo in class 12 IBB in two meetings held on 29 August – 05 September 2023. This research uses a qualitative descriptive method. Data collection techniques by observing and noting the results are: I'm sick, come on, just do my homework, please do it, I'll let you go, I'm sleepy, I don't know, stop first, I forgot I was in a hurry, I didn't eat, why didn't I come in, I'm sleeping, my grades have to be good, I'm afraid.